Participative management in workers' health: an experience in the vector control activity - Vilela, Rodolfo Andrade de Gouveia; Malagoli, Maria Elizabeth; Morrone, Luiz Carlos (Saúde e Sociedade, 2010)
INTRODUCTION: The paper shows the implementation experience of a management system in occupational health that took place at SUCEN (Superintendence for Endemic Control), from 1998 to 2002, which worked on the activity of chemical control of vectors in the State of São Paulo. OBJECTIVE: To describe the participative management system, the actions that were taken and the main accomplished results. METHODS: Report on what was experienced by the team using qualitative approach, document analysis and report on quantitative data. RESULTS: Eleven COMSAT's (Workers Health Committees) were elected, which, together with the technical team, started to identify the occupational risks and proposals to prevent and control them. The investigation resulted in 650 suggestions, 45.7% of which were carried out. Work-related diseases were identified as allergic reactions to pesticides, muscular pain linked to repetitive movements, hearing disorders and back pain caused by excessive weight carrying. A total of 1003 workers participated in the basic courses on workers health, 90.8% of whom classified them as good or excellent. CONCLUSIONS: The participative management system puts into practice the democratic management principles of SUS (Brazil's National Health System); by means of risk mapping, it incorporates workers' experiences; it regards workers as agents in the change and negotiation process; it puts into practice the right to information. The COMSAT's proved to be adequate places for negotiating improvements in working conditions. The approval of the Management System ended up in legal validation through a three-party agreement signed in March 2002.